Mechanisms of unprimed and dexamethasone‐primed nonviral gene delivery to human mesenchymal stem cells. Issue 2 (7th December 2018) - Hamann, Andrew; Broad, Kelly; Nguyen, Albert; Pannier, Angela K.
Abstract: Human mesenchymal stem cells (hMSCs) are under intense study for applications of cell and gene therapeutics because of their unique immunomodulatory and regenerative properties. Safe and efficient genetic modification of hMSCs could increase their clinical potential by allowing functional expression of therapeutic transgenes or control over behavior and differentiation. Viral gene delivery is efficient, but suffers from safety issues, while nonviral methods are safe, but highly inefficient, especially in hMSCs. Our lab previously demonstrated that priming cells before delivery of DNA complexes with dexamethasone (DEX), an anti‐inflammatory glucocorticoid drug, significantly increases hMSC transfection success. This work systematically investigates the mechanisms of hMSC transfection and DEX‐mediated enhancement of transfection. Our results show that hMSC transfection and its enhancement by DEX are decreased by inhibiting classical intracellular transport and nuclear import pathways, but DEX transfection priming does not increase cellular or nuclear internalization of plasmid DNA (pDNA). We also show that hMSC transgene expression is largely affected by pDNA promoter and enhancer sequence changes, but DEX‐mediated enhancement of transfection is unaffected by any pDNA sequence changes. Furthermore, DEX‐mediated transfection enhancement is not the result of increased transgene messenger RNA transcription or stability. However, DEX‐priming increases total protein synthesis by preventing hMSC apoptosis induced by transfection, resulting in increased translation of transgenic protein. DEX may also promote further enhancement of transgenic reporter enzyme activity by other downstream mechanisms. Mechanistic studies of nonviral gene delivery will inform future rationally designed technologies for safe and efficient genetic modification of clinically relevant cell types. Abstract : Human mesenchymal stem cells (hMSCs) are under intense study for applications of cell and gene therapeutics because of their unique immunomodulatory and regenerative properties. Safe and efficient genetic modification of hMSCs could increase their clinical potential by allowing functional expression of therapeutic transgenes or control over behavior and differentiation.